Proceedings of the 9th International Workshop on Automation of Software Test 2014
DOI: 10.1145/2593501.2593507
|View full text |Cite
|
Sign up to set email alerts
|

Effective unit-testing in model-based software development

Abstract: Model-based software development is extensively used in avionics and automotive safety critical control software applications. In model-based software development, highly optimized code is generated automatically from models. Such code is often hard to understand and this can make it difficult to write test cases. Therefore, in model based software development, test cases have to be derived based on the models to achieve coverage of code auto-generated from the models. Further, safety standards in those domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Further, test design techniques have significant effect on productivity in model based software development. Our other work [17] showed that exploratory testing used in this study is least productive in model based software development. In our future work, we would also like to analyze the productivity of enhancement tasks using other test design techniques.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Further, test design techniques have significant effect on productivity in model based software development. Our other work [17] showed that exploratory testing used in this study is least productive in model based software development. In our future work, we would also like to analyze the productivity of enhancement tasks using other test design techniques.…”
Section: Discussionmentioning
confidence: 72%
“…Unlike traditional software, enhancement tasks in model based development requires testing the model as well as the auto-generated code from the model to ensure required functionality is captured competently and auto-generated code is suitable to the target platform [17].…”
Section: Enhancements In Model Based Softwarementioning
confidence: 99%
See 1 more Smart Citation